2019
DOI: 10.29328/journal.apps.1001017
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antibiotic residue in poultry in Kathmandu valley of Nepal: A cross-sectional study

Abstract: This cross-sectional study was conducted to screen the presence of antibiotic residue in poultry. A total of 60 samples (30 Muscle and 30 Liver) were taken from local meat shops from different parts of Kathmandu valley. Disc assay method was used. Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 25923) were used as test organisms. The results revealed 8 positive samples (which is 13%). Among 30 Liver samples, 3 showed positive result, while only 2 muscle sample indicated positive result. Muscle ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Disregard for withdrawal periods may result in antimicrobial residue contamination in the food supply that can expose consumers to unknown levels of antimicrobials. Several studies in Nepal have demonstrated antimicrobial residues in sampled meat ranging from 13% up to 62% [28,29]. Although cooking temperatures destroy antimicrobial residues in meat, inadequately cooked meat may result in antimicrobial residue consumption and two major negative outcomes: antimicrobial resistance development and adverse drug reactions [21].…”
Section: Discussionmentioning
confidence: 99%
“…Disregard for withdrawal periods may result in antimicrobial residue contamination in the food supply that can expose consumers to unknown levels of antimicrobials. Several studies in Nepal have demonstrated antimicrobial residues in sampled meat ranging from 13% up to 62% [28,29]. Although cooking temperatures destroy antimicrobial residues in meat, inadequately cooked meat may result in antimicrobial residue consumption and two major negative outcomes: antimicrobial resistance development and adverse drug reactions [21].…”
Section: Discussionmentioning
confidence: 99%
“…In consistence with the observation of the present study, prevalence of antimicrobial residues in broiler chicken has earlier been recorded in many developing countries. For instance, Nonga et al (2009) and Shareef et al (2009) reported 70% and 52% antibiotic residues in broiler chicken respectively, while Sapkota et al (2019) and Raut et al (2017) reported a lower rate of 13% in Kathmandu valley and 22% in Nepal. Sapkota et al (2019) explained that the differences in results could be due to various reasons, such as the use of different bacteria as test organism and their varied susceptibility to different antibiotics, inconsistencies in sample size, the variation of the practice of antibiotic use in different locations and differences in the methods for detection.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a separate study conducted at Gorkha, Parsa, Chitwan, and Kathmandu districts with broiler meat detected as high as 40% (32/80) penicillin, aminoglycoside, and Tetracyclines by the rapid test kit (Rawal, 2015). Another cross-sectional study conducted in Kathmandu valley in 2019, by the use of disc assay methods, detected 13.33 (8/60) poultry meat samples by Sapkota et al (2019).…”
Section: Research Articlementioning
confidence: 99%